Terminologi dan Aspek-aspek Collaborative Problem Solving Skill’s - Miksan Ansori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
Collaborative problem solving is one of a series of abilities that are needed in the 21st century in various aspects of life such as work, community, organization and even in the family. If it is not instilled early on, this ability will not be owned by a person given the flow of globalization and technological development, communication and information in many studies actually gives the effect of exlusivism, individualism and low social attitudes that make it difficult for them to collaborate in solving increasingly complex problems. Discourse on Collaborative Problem Solving in various aspects is needed. In addition to strengthening and developing science, studies on CPS are needed to further strengthen practitioners to implement them. Before proceeding further in the application and development of Collaborative Problem Solving skills, the meaning and aspects must be clearly known first.